Performance of Three Adelphocoris spp. (Hemiptera: Miridae) on Flowering and Non-flowering Cotton and Alfalfa - Zhen GAO; Hong-sheng PAN; Bing LIU; Yan-hui LU; Ge-mei LIANG (Journal of Integrative Agriculture)
The genus Adelphocoris (Hemiptera: Miridae) is a group of key insect pests in cotton fields in China that includes three dominant species: A. suturalis (Jakovlev), A. lineolatus (Goeze) and A. fasciaticollis (Reuter). Previous field surveys have found that adults of these Adelphocoris species usually move onto specific host plants when the plants enter the flowering stage. To determine the potential trade-offs for this host-plant preference behavior, the performance of these three Adelphocoris spp. on flowering and non-flowering cotton and alfalfa were compared in the laboratory. The results showed that Adelphocoris spp. had significantly higher nymphal developmental and survival rates, along with increased adult longevity and fecundity on flowering cotton and alfalfa than on non-flowering plants of either species. In addition, compared with cotton plants, alfalfa generally promoted better performance of these three Adelphocoris species, especially for A. lineolatus. Simple correlation analysis indicated that female adult longevity was positively correlated to male adult longevity and female fecundity, and female fecundity was positively correlated to nymphal development and survival rates. This study demonstrated a positive correlation between adult preference and offspring/adult performance for all three Adelphocoris species, with no evidence of any trade-offs for this preference for flowering host plants. These findings support the hypothesis that hemimetabolous insects such as mirid bugs have positive adult preference-adult/nymphal performance relationships, which is likely due to the similar feeding habits and nutritional requirements of adults and nymphs.